1978
DOI: 10.1056/nejm197803232981202
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function after Surgical Treatment of Thyrotoxicosis

Abstract: We assessed thyroid function for 12 months after subtotal thyroidectomy in 100 tyrotoxic patients treated with propranolol alone before and immediately after operation. The operation proved safe, with low morbidity. Suppression of the hypothalamic-pituitary-thyroid axis, present in the majority one month after operation, was evidenced by normal or low levels of serum total tri-iodothyronine and thyroxine, but absent or subnormal serum thyrotropin response to thyrotropin-releasing hormone. Eighty patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Serum TSH was measured by RIA; the between-assay coefficient of variation using anonymous control sera was 5.1% (7). In euthyroid patients attending an Endocrine Clinic, the 95th percentile of TSH concentrations was 5.7 mU/liter, which was therefore regarded as the upper limit of the reference (normal) range, with 5% of patients having concentrations between 5.7-10 mU/liter.…”
Section: Methodsmentioning
confidence: 99%
“…Serum TSH was measured by RIA; the between-assay coefficient of variation using anonymous control sera was 5.1% (7). In euthyroid patients attending an Endocrine Clinic, the 95th percentile of TSH concentrations was 5.7 mU/liter, which was therefore regarded as the upper limit of the reference (normal) range, with 5% of patients having concentrations between 5.7-10 mU/liter.…”
Section: Methodsmentioning
confidence: 99%
“…This incidence was lower than that reported by Toft et a1., who found that 80% were euthyroid 12 months after surgery [11]. In another series reported by the Noguchi Thyroid Clinic and Hospital Foundation, however, 90.6% became euthyroid after surgery [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the low euthyroid rate observed in the present study might have been due to sampling errors independent of the current hypothesis. The presence of 11 censored cases (most of them were considered to be euthyroid), selection of enlarged thyroid glands to obtain enough amount of thyroid tissue for culture study, and the shortness of the observation periods after the surgery [11] might be related to the higher incidence of post-operative hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since propranolol is now commonly used pre-and perioperatively for hyperthyroidism (1)(2)(3)(4)(5), it seems important to keep in mind the propranolol-induced modulations of the cardiovascular responses to stress in the event of various emergencies.…”
mentioning
confidence: 99%